2021
DOI: 10.1186/s12942-021-00272-2
|View full text |Cite
|
Sign up to set email alerts
|

Cycling in one of the most polluted cities in the world: Exposure to noise and air pollution and potential adverse health impacts in Delhi

Abstract: Background In India, many cities struggle with extreme levels of air pollution and noise. Delhi, in particular, has the notorious reputation of being one of the most polluted cities in the world. Cyclists constitute a particularly exposed population, since they cycle among motor vehicles without any protection. This paper modeled the cyclists’ exposure to nitrogen dioxide (NO2) and noise in Delhi, India. Methods Using primary data collected on 1,22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…These factors would trigger adverse health impacts on them, such as respiratory and cardiovascular diseases, certain types of cancer, annoyance, and stress. According to the study done by Apparicio et al, cyclists could reach the daily mean noise exposure of dB Laden in 29, 21, and 13 min on a residential street, tertiary road, and primary road in an area with moderate predicted values of noise; they could also intake risk value of NO2 per hour in 27, 24, 23 min on a residential street, tertiary road, and primary road [15].…”
Section: Extremely Polluted Environmentmentioning
confidence: 97%
“…These factors would trigger adverse health impacts on them, such as respiratory and cardiovascular diseases, certain types of cancer, annoyance, and stress. According to the study done by Apparicio et al, cyclists could reach the daily mean noise exposure of dB Laden in 29, 21, and 13 min on a residential street, tertiary road, and primary road in an area with moderate predicted values of noise; they could also intake risk value of NO2 per hour in 27, 24, 23 min on a residential street, tertiary road, and primary road [15].…”
Section: Extremely Polluted Environmentmentioning
confidence: 97%
“…Despite the overall health effects of noise, exposure to noise during cycling has remained an understudied topic [30]. Studies from Delhi, Montreal and from eleven Dutch cities found that the cyclists were exposed to excessive noise in these cities [58][59][60]. In one study, noise exposure of cycling was found to be the highest along major roads and downtown [31].…”
Section: Noise and Cyclingmentioning
confidence: 99%